Dielectric Properties of High Alumina Glass - Farid, S. B. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
High Alumina Glasses "Alumina Silicate Glasses" was prepared by utilizing powder technology technique. The starting materials are wasted soda-lime glass from an industrial site, IraqiÂ Duekhla raw kaolin and small amounts of potassium carbonates. X-ray Diffraction and FTIR analysis show complete vitreous glasses are obtained. Increasing Alumina content plays an obvious role in improving physical and mechanical properties of the prepared high alumina glass. In addition, the increased alumina content enhanced the dielectric constant and reduced dielectric loss. These results may be interpreted as due to the bridging bonding of alumina with both the silica and the alkali oxides; which impedes the alternating electric field.